2022
DOI: 10.1108/rpj-07-2021-0184
|View full text |Cite
|
Sign up to set email alerts
|

Thermal modeling of directed energy deposition additive manufacturing using graph theory

Abstract: Purpose The purpose of this paper is to develop, apply and validate a mesh-free graph theory–based approach for rapid thermal modeling of the directed energy deposition (DED) additive manufacturing (AM) process. Design/methodology/approach In this study, the authors develop a novel mesh-free graph theory–based approach to predict the thermal history of the DED process. Subsequently, the authors validated the graph theory predicted temperature trends using experimental temperature data for DED of titanium all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…The gas metal arc-based directed energy deposition (GMA-DED) process exhibits a very high deposition rate and negligible material waste compared to other forms of metal additive manufacturing (AM) processes (Alfattni, 2022; Lidong and Alexander, 2016; Riensche et al , 2023). However, it experiences high heat input during the deposition of layers and yields significant residual stress (RS) in the component, which can further cause the distortion of the substrate (Özdemir and Korkmaz, 2023; Williams et al , 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The gas metal arc-based directed energy deposition (GMA-DED) process exhibits a very high deposition rate and negligible material waste compared to other forms of metal additive manufacturing (AM) processes (Alfattni, 2022; Lidong and Alexander, 2016; Riensche et al , 2023). However, it experiences high heat input during the deposition of layers and yields significant residual stress (RS) in the component, which can further cause the distortion of the substrate (Özdemir and Korkmaz, 2023; Williams et al , 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the excellent weldability of maraging steels due to their low carbon content makes them highly suitable for additive manufacturing (AM), where rapid cooling rates can induce a martensitic structure during fabrication. Laser-directed energy deposition (DED) is one of the most widely utilized AM techniques which offers multiple advantages over other traditional manufacturing techniques such as near-net-shape parts, a low buy-to-fly ratio, large scale Metals 2023, 13, 1214 2 of 11 printing and, most importantly, the repair of worn or damaged parts [10][11][12][13][14][15][16]. DED is a powder-based deposition process, where a powder and laser are simultaneously passed on the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to reduced cost, AM processes have the potential to become fully automated. Research has demonstrated a strong desire to develop fully automated metal AM techniques with rapid modeling capabilities to reduce the potential of defects and ensure quality standards of parts is achieved [6,7]. In [8], Panchagnula and Simhambhatla highlight the ability of the metal AM process to produce complex designs including sudden overhang features (features that are perpendicular to the deposition direction or nearly horizontal features) without support material.…”
Section: Introductionmentioning
confidence: 99%